PENGARUH CETAKAN BRIKET TERHADAP KARAKTERISTIK BRIKET PADA MESIN PRESS HIDROLIK - Angger Bagus Prasetiyo; Sutrisna; Dandung Rudy Hartana; Iman Pradana A. Assagaf; Kartinasari Ayuhikmatin Sekarjati; Aldi Sinar Saputro; Dominggus Daniel Lefmanut; Aditya Rahayu (Scientific Journal of Mechanical Engineering Kinematika, 2025)
To create briquettes, the raw materials are compressed using a variety of pressing pressures. Briquette presses come in two popular varieties: vertical and horizontal. Briquettes are often made from non-hazardous home waste and agricultural biomass, offering a premium and sustainable alternative energy source. The goal of this study was to use a hydraulic press-type briquette press method to improve the shape properties of the briquettes. The ingredients employed in this investigation were water, tapioca, wood dust, and rice husk. The composition of the briquettes is 40% rice husk, 40% sawdust, 10% tapioca, and 10% water. A hydraulic press machine with a maximum pressure of 30 Psi was utilized in the briquette press method. This study will examine each mold's density, drop test, water resistance, and burning rate. According to this study, triangular briquettes have the lowest briquette burning rate value (0.1 g/min), the lowest impact resistance value (0.67%), the slowest burning rate value (0.1 g/min), which indicates longer burning, and the highest value (0.9696 g/cm³), which indicates a denser and more solid structure. According to the findings of the test criteria that researchers have conducted, triangular briquettes are recommended.